1996
DOI: 10.1006/nimg.1996.0033
|View full text |Cite
|
Sign up to set email alerts
|

The Trouble with Cognitive Subtraction

Abstract: In this paper we present a critique of pure insertion. Pure insertion represents an implicit assumption behind many (but not all) studies that employ cognitive subtraction. The main contention is that pure insertion is not valid in relation to the neuronal instantiation of cognitive processes. Pure insertion asserts that there are no interactions among the cognitive components of a task. It is possible to evaluate and refute this assumption by testing explicitly for interactions using factorial experimental de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
297
1
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 499 publications
(303 citation statements)
references
References 23 publications
1
297
1
3
Order By: Relevance
“…Images were smoothed with a (12 mm FWHM) Gaussian kernel filter. The analysis of the functional imaging data entailed the creation of parametric maps representing a statistical assessment of hypothesized condition-specific activity using the general linear model approach [16]. A within-participants analysis was performed with identical models across participants.…”
Section: Methodsmentioning
confidence: 99%
“…Images were smoothed with a (12 mm FWHM) Gaussian kernel filter. The analysis of the functional imaging data entailed the creation of parametric maps representing a statistical assessment of hypothesized condition-specific activity using the general linear model approach [16]. A within-participants analysis was performed with identical models across participants.…”
Section: Methodsmentioning
confidence: 99%
“…The findings of these previous imaging studies suggested a specific role of the lateral prefrontal cortex (LPFC) for dual-task processing (D'Esposito, Detre, Alsop, Shin, Atlas, & Grossman, 1995;Goldberg et al, 1998;Schubert & Szameitat, 2003; but see Jiang, Saxe, & Kanwisher, 2004). Specifically, these studies compared the fMRI activation in dual-task blocks with the activation when participants performed the component tasks in single-task blocks, thereby employing the method of cognitive subtraction (Friston, Price, Fletcher, Moore, Frackowiak, & Dolan, 1996). The finding of an overadditive activation in prefrontal regions was interpreted as being related to additional cognitive demands present in the dual task, as compared to the summed demands of both single tasks.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the hemodynamic effect of such thoughts using the subtraction method has been demonstrated in a tone task (Binder et al, 1999). Moreover, depending on the statistical approach, subtraction or other, results can differ markedly (Friston et al, 1996). The subtraction method assumes "pure insertion", that the cognitive process is "irrespective of the cognitive or physiological context" (Friston et al, 1996), an assumption which may not be valid.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, depending on the statistical approach, subtraction or other, results can differ markedly (Friston et al, 1996). The subtraction method assumes "pure insertion", that the cognitive process is "irrespective of the cognitive or physiological context" (Friston et al, 1996), an assumption which may not be valid. Indeed, the two fMRI papers in schizophrenia compared groups on standard and deviant tones separately, thus avoiding the difficulties of the subtraction method in an fMRI environment (Wible et al, 2001;Kircher et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation